COMPARING ROUTES OF KETAMINE ADMINISTRATION IN TREATMENT-RESISTANT DEPRESSION: EFFICACY, SAFETY, AND OPTIMIZATION OF DOSING STRATEGIES - Grygutis, Irmina; Mikołajczyk, Oskar; Fimiarz, Kornelia Julia; Jarzęcka, Urszula; Łysak, Kinga; Pawełkiewicz, Sonia; Wójcik, Kamil; Serafin, Aleksandra; Baran, Karolina; Podolak, Maja (International Journal of Innovative Technologies in Social Science, 2026)
Background: Treatment-resistant depression (TRD) is associated with substantial functional impairment, suicide risk, and health-care costs. Ketamine and its S-enantiomer, esketamine, have emerged as rapid-acting glutamatergic treatment options for TRD.Aim: This review aims to synthesize current evidence on the different ketamine administration routes for TRD, with a focus on acute and maintenance efficacy, dosing strategies, safety, infrastructure needs, and positioning within stepped-care algorithms.Methods: A narrative review of randomized controlled trials, meta-analyses, systematic reviews, and long-term open-label studies was performed. Outcomes were grouped by route and examined for (1) antidepressant response, (2) adverse-event profile, (3) required clinical resources, and (4) integration with other treatments such as electroconvulsive therapy and psychotherapy.Results: Ketamine and esketamine can be administered via intravenous (IV), intranasal (IN), oral, subcutaneous (SC), and intramuscular (IM) routes. IV racemic ketamine shows the strongest and fastest antidepressant effect but demands infusion-suite equipment and monitoring for transient hypertension and dissociation. FDA-approved IN esketamine offers robust long-term data but requires administration under supervised in-clinic administration and blood pressure monitoring. According to the reviewed studies, IV and IN routes remain the best-supported options for achieving a rapid response. Oral, sublingual and extended-release formulations provide easier access and lower cost, but have reduced bioavailability, modest effect sizes, and higher diversion risk. These routes of administration may be useful for maintenance treatment in resource-constrained settings. SC and IM injections achieve ~90 % bioavailability with minimal infrastructure, yet evidence is limited to small series.Conclusion: The optimal ketamine route is context-dependent, and requires balancing efficacy, safety, cost, and health-system capacity.  Future research should include direct comparative trials and extended safety monitoring to better define the long-term efficacy, tolerability, and optimal clinical use of different ketamine administration routes.